Comparison of Two Staining Methods for Pollen Viability Studies in Sugarcane - Melloni, Maria Letícia G. [UNESP]; Scarpari, Maximiliano S.; de Mendonça, Jeremias R.; Perecin, Dilermando [UNESP]; de Andrade Landell, Marcos G.; Pinto, Luciana R. (Springer Nature, 2013)
The present work aimed to compare two staining methods for pollen viability evaluation in sugarcane. Pollen from four sugarcane genotypes were collected at three different times (6.00, 8.00 and 9.00 a.m.) and tested for viability using two staining methods (iodine and lactophenol blue). Three anthers, of each genotype were crushed in a glass slide with a drop of the respective stain (iodine 0.1 N and lactophenol blue). The percentage of pollen viability was obtained with an optic microscope (250×) and compared with the pollen germination at culture media where one raquis of each genotype was gentle shaken in a petridish. Three replicates (petri dishes) was performed for each genotype which were maintained at the temperature of 25 °C and air humidity around 95 % for 30 min. The factors (staining methods, genotypes and times) and their interactions were evaluated by the analysis of variance, F test (P < 0.01) and the means compared by the t test (P < 0.05). The lactophenol blue staining was more sensible than the iodine staining method to detect the decrease of pollen viability which occurs naturally in sugarcane. The iodine staining method was more stable and easier than lactophenol to perform the inflorescence classification at any evaluated time (6.00, 8.00 and 9.00 a. m.). Both staining methods overestimated the viability obtained by the germination at culture media when performed at 6.00 a.m. © 2012 Society for Sugar Research & Promotion.
Keywords: Breeding; Hybridization; Iodine; Lactophenol; Pollen germination